Antiallergic Effects of N,N-dicoumaroylspermidine Isolated from Lithospermum erythrorhizon on Mast Cells and Ovalbumin-Induced Allergic Rhinitis - Le, Tam Thi; Kang, Tae Kyeom; Lee, Wook-Bin; Jung, Sang Hoon (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In East Asia, the dried root of Lithospermum erythrorhizon has been utilized as an anti-inflammatory, antipyretic, detoxifying, and anti-inflammatory agent. Recently, we reported that L. erythrorhizon protects against allergic rhinitis; however, the component within L. erythrorhizon that exerts antiallergic activity remains unknown. The purpose of the current study was to isolate and characterize the antiallergic active components in an ethanolic extract of L. erythrorhizon roots. We examined the antiallergic effects of L. erythrorhizon reflux ethanol extracts in an ovalbumin (OVA)-induced allergic rhinitis mouse model, and compared the chemical compounds extracted using the hot reflux and cold extraction methods. Chromatographic separation identified two novel anthraquinones, erythrin A and B, one newly discovered compound from the Lithospermum genus, N1 '',N3 ''-dicoumaroylspermidine, and nineteen other recognized compounds. Their chemical structures were elucidated by single (1D) and 2D analysis of nuclear magnetic resonance (NMR) spectroscopic data, as well as high resolution mass spectrometry. Among the identified compounds, N,N'-dicoumaroylspermidine strongly inhibited the release of beta-hexosaminidase, as well as the production of IL-3, IL-4, and IL-13 by IgE-sensitized and BSA-stimulated RBL-2H3 cells. Using the OVA-induced allergic rhinitis mouse model, we showed that N,N'-dicoumaroylspermidine reduced the production of serum OVA-specific IgE and the number of inflammatory cells in nasal lavage fluid. N,N'-dicoumaroylspermidine isolated from L. erythrorhizon exhibits antiallergic properties, making it potentially effective for allergic rhinitis.